2018
DOI: 10.1080/23328940.2018.1493907
|View full text |Cite
|
Sign up to set email alerts
|

Occupational cooling practices of emergency first responders in the United States: A survey

Abstract: Despite extensive documentation directed specifically toward mitigating thermal strain of first responders, we wished to ascertain the degree to which first responders applied cooling strategies, and what opinions are held by the various agencies/departments within the United States. An internet-based survey of first responders was distributed to the International Association of Fire Chiefs, International Association of Fire Firefighters, National Bomb Squad Advisory Board and the USA Interagency Board and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…As there is no one size fits all approach, it is important for key stakeholders to synthesize the relevant resources and literature in order to implement the most pragmatic means of cooling for their workers. With the final decision based upon gauging the occupations specific needs including, the threshold for risk of heat stress (Carter R. et al, 2007), employee characteristics (McGregor et al, 2015; National Institute for Occupational Safety and Health, 2016), expected work durations (National Institute for Occupational Safety and Health, 2016), logistics and preparation time typically available (Bach et al, 2018), allowances for recovery (Carter J.M. et al, 2007), department budgetary constraints (Phuong et al, 2013; Bach et al, 2018), cooling system functionality and integration (Adams et al, 1994; Chan et al, 2013), seasonal and geographic considerations (Carter J.M.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is no one size fits all approach, it is important for key stakeholders to synthesize the relevant resources and literature in order to implement the most pragmatic means of cooling for their workers. With the final decision based upon gauging the occupations specific needs including, the threshold for risk of heat stress (Carter R. et al, 2007), employee characteristics (McGregor et al, 2015; National Institute for Occupational Safety and Health, 2016), expected work durations (National Institute for Occupational Safety and Health, 2016), logistics and preparation time typically available (Bach et al, 2018), allowances for recovery (Carter J.M. et al, 2007), department budgetary constraints (Phuong et al, 2013; Bach et al, 2018), cooling system functionality and integration (Adams et al, 1994; Chan et al, 2013), seasonal and geographic considerations (Carter J.M.…”
Section: Discussionmentioning
confidence: 99%
“…With the final decision based upon gauging the occupations specific needs including, the threshold for risk of heat stress (Carter R. et al, 2007), employee characteristics (McGregor et al, 2015; National Institute for Occupational Safety and Health, 2016), expected work durations (National Institute for Occupational Safety and Health, 2016), logistics and preparation time typically available (Bach et al, 2018), allowances for recovery (Carter J.M. et al, 2007), department budgetary constraints (Phuong et al, 2013; Bach et al, 2018), cooling system functionality and integration (Adams et al, 1994; Chan et al, 2013), seasonal and geographic considerations (Carter J.M. et al, 2007; Hanna et al, 2011; McGregor et al, 2015; Nunfam et al, 2018), and the workplace capacity to measure the environment and the worker (McGregor et al, 2015; National Institute for Occupational Safety and Health, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Traffic police officers have been found to have significant changes in blood pressure and heart rate (An et al, 2020), as well as heat stress symptoms like fatigue, cramps, and dizziness (Rasdi et al, 2017). Studies have found that firefighters can experience heat stress up to 20 times per year (Kim et al, 2019) and that many U.S. first responders agencies experience cases of heat illness regularly, with 39% of fire departments and 18% of law enforcement departments having at least one case of heat illness within the previous year (Bach et al, 2018). Despite this, nearly a quarter of the surveyed agencies provide no cooling mitigation or recovery resources (Bach et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that firefighters can experience heat stress up to 20 times per year (Kim et al, 2019) and that many U.S. first responders agencies experience cases of heat illness regularly, with 39% of fire departments and 18% of law enforcement departments having at least one case of heat illness within the previous year (Bach et al, 2018). Despite this, nearly a quarter of the surveyed agencies provide no cooling mitigation or recovery resources (Bach et al, 2018). Climate change adaptation and preparedness plans need to account for the increased need of a broad number of societal services and these attendant consequences, like heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, the present study showed the addition of slushy ingestion to IV further reduced thermoregulatory strain (Table 2, Figure 2A) which benefited the cardiovascular system (Table 4, Figure 2C). It is reported end-users do not utilise cooling methods before or during work as frequently as following work (52). Whether this is due to time and/or education is currently unknown, though logistics and time constraints are often cited as barriers to cooling method use (52).…”
Section: Physiological Variablesmentioning
confidence: 99%